Report of a case with gallbladder carcinoma: P53 expression of the peritumor epithelium might predict biliary tract recurrence. (2016) - Takano, Atsushi; Nakagomi, Hiroshi; Ikegame, Kou; Yamamoto, Atsushi; Watanabe, Hideki; Nakada, Haruka; Inoue, Masayuki; Sugai, Hidemitsu; Yasutome, Michiya; Furuya, Kazushige; Hada, Masao; Miyasaka, Yoshiaki; et al.
Highlights: The over-expression of P53 protein in gallbladder carcinoma is a biomarker correlating with a poor survival. However, the significance of P53 expression in peritumor tissues is unknown. We report a case of gallbladder carcinoma where the operative specimen showed over-expression of P53 on the peritumor epithelium, and early recurrence developed at the biliary tract. The immunohistochemical staining of the GB wall or surgical stump for a surgical specimen of GBC may be crucial to predict the bile duct recurrence. Abstract: Introduction: The over-expression of P53 protein in gallbladder carcinoma is a biomarker correlating with a poor survival. However, the significance of P53 expression in peritumor tissues is unknown. We experienced a case of gallbladder carcinoma where the operative specimen showed over-expression of P53 on the peritumor epithelium, and early recurrence developed at the biliary tract. Presentation of case: A 74-year-old female patient was referred to our hospital due to wall thickening of the gallbladder on ultrasonography. Radiographic examinations revealed wall thickening at the fundus of gallbladder and no abnormalities of the biliary tract or surrounding lymph nodes. We performed open cholecystectomy and lymph node dissection without extrahepatic bile duct resection, as a frozen section of the surgical stump of the cystic duct was cancer-free. However, a pathological examination revealed over-expression of P53 protein in the epithelium of the peritumor to the cystic duct, which were diagnosed as normal on hematoxylin eosin staining. The patient developed bile duct metastases, two and half years after the operation. She underwent endoscopic stenting for the obstruction of bile duct with no additional therapy, and died 6 months later. Discussion and conclusion: The immunohistochemical staining of the GB wall or surgical stump for a surgical specimen of GBC may be crucial to predict the bile duct recurrence.